3D printed device for epitachophoresis - Voráčová, Ivona; Přikryl, Jan; Novotný, Jakub; Datinská, Vladimíra; Yang, Jaeyoung; Astier, Yann; Foret, František (Analytica chimica acta, 2021)
Polyacrylamide or agarose gels are the most frequently used sieving and stabilizing media in slab gel electrophoresis. Recently, we have introduced a new electrophoretic technique for concentration/separation of milliliter sample volumes. In this technique, the gel is used primarily as an anticonvection media eliminating liquid flow during the electromigration. While serving well for the liquid stabilization, the gels can undergo deformation when exposed to a discontinuous electrolyte buffer system used in epitachophoresis. In this work, we have explored 3D printing to form rigid stabilizing manifolds to minimize liquid flow during the epitachophoresis run. The whole device was printed using the stereolithography technique from a low water-absorbing resin. The stabilizing manifold, serving as the gel substitute, was printed as a replaceable composite structure preventing electrolyte mixing during the separation. Different geometries of the 3D printed stabilizing manifolds were tested for use in concentrating ionic sample components without spatial separation. The presented device can focus analytes from 3 or 4 mL of the sample to 150 μL or less, depending on the collection cup size. With the 150 μL collection cup, this represents the enrichment factor from 20 to 27. The time of concentration was from 15 to 25 min, depending on stabilization media and power used.
Keywords: 3D printing; Electromigration method; Epitachophoresis; Sample concentration